Integrating Islamic Ethical Principles into AI Education and Character Building in Digital Society - Yahya Shaykh Ahmad; Yusuf Abdulrasaq; Ali Miqdad Ali; Farman Ali (Tuah Foundation, 2025)
The rapid evolution of artificial intelligence (AI) presents unprecedented ethical challenges concerning fairness, transparency, and privacy in digital societies. While the global discourse on AI ethics has proliferated, it remains predominantly shaped by secular Western-centric frameworks, creating a significant gap in pluralistic and culturally grounded ethical perspectives. This conceptual study addresses this gap by systematically exploring how the rich ethical tradition of Islam can provide a robust normative framework for enhancing the moral capabilities of AI. Employing a qualitative hermeneutic methodology, the research analyzes primary Islamic sources (the Qur’an and Sunnah) alongside classical and contemporary scholarship to articulate three cardinal ethical principles: 'adl (comprehensive justice), transparency rooted in amanah (sacred trust), and privacy as ḥurma (inviolable right). The findings demonstrate that these principles offer direct, actionable guidance to rectify prevalent AI ethical failures, including algorithmic bias, opaque decision-making, and exploitative data practices. Moreover, this study emphasizes the integration of these principles into AI education and character building, proposing curriculum models that cultivate ethical awareness, digital citizenship, and moral responsibility. By translating timeless Islamic ethics into contemporary technical and educational imperatives, this paper contributes a vital, culturally resonant perspective to the global AI ethics dialogue, advocating for interdisciplinary collaboration between AI developers, policymakers, and Islamic ethicists to foster equitable, transparent, and human-centered AI systems.